The Effect of BPJS Kesehatan Smart Claim Implementation on Service Efficiency and Effectiveness at Santa Elisabeth Hospital Medan - Bima Roy Manullang; Felix Kasim; Sri Melda Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
BPJS Kesehatan Smart Claim implementation at Santa Elisabeth Hospital Medan has progressed to Star 4, including online pharmacy bridging or e-prescription integration. This study aimed to analyze the effect of this implementation on service efficiency and effectiveness. It used a qualitative approach with an intrinsic case study design. Eighteen informants were selected through purposive-homogeneous sampling. Data were collected from August to December 2025 through semi-structured in-depth interviews, limited participatory observation of the end-to-end service and claim workflow, and document review. The data were analyzed thematically using methodological and theoretical triangulation. The findings show that Smart Claim improves data access, supports partial paperless processes, and accelerates service and claim processes under certain conditions. The claim cycle is perceived to be shorter, and pharmacy processing becomes faster after e-prescription integration. Tangibles and responsiveness tend to improve, whereas reliability and assurance still fluctuate during network and bridging disruptions, slow devices, and data mismatch or mapping problems that trigger rework, cross-unit escalation, and pending or returned claims. This study concludes that Smart Claim improves service efficiency and effectiveness conditionally, depending on infrastructure stability, staff readiness, and claim data governance.